FISCAL POLICY MANAGEMENT AND PRIVATE INVESTMENT IN NIGERIA: CROWDING-OUT OR CROWDING-IN EFFECT? - Awode, Segun Subair (Universitas Muhammadiyah Yogyakarta, 2019)
The Nigerian government over the years embarked on diverse macroeconomic policy options to tinker the economy on the path of growth and development. Amongst the policy options readily employed is that of fiscal policy. Despite the lofty place of fiscal policy in the management of the Nigerian economy, the economy is yet to come on the path of sound growth and development. The intent of fiscal management is essentially to stimulate economic and social development by pursuing a policy stance that ensures a sense of balance between taxation, expenditure and borrowing that is consistent with sustainable growth. However, the extent to which fiscal management engenders private investment continues to attract theoretical and empirical debate especially in developing countries like Nigeria. In light of this, the present study fills the gap by examining the relationship between fiscal management and private investment in Nigeria between 1987 and 2015. The study employed ex-post facto research design. Secondary time series data were used for the study and these were sourced from CBN statistical bulletin and World Development Indicators, 2015. The data collected were analyzed using the Autoregressive Distributed Lag with inferences drawn at 5% significance level. The result of the relationship between fiscal management and private investment in Nigeria showed that inflation, capital expenditure, indirect tax and non-tax revenue had positive and significant effects on private investment (Î²=0.02, t=19.04; Î²=0.59, t=40.13; Î²=1.70, t=17.07; Î²=1.05, t=22.03 respectively) in Nigeria, while domestic credit to private sector had negative but significant effect on private investment (Î² = -0.09, t = -17.26) in Nigeria within the period. The study concluded that a crowding-in relationship exists between capital expenditure and private investment, while indirect tax revenue has significant and non-distortionary relationship with private investment. The study therefore recommends more public investment in capital projects and that the tax system should generally be made favorable towards private sector investment.